MEKANISME DAN EFEKTIVITAS MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN DALAM SENGKETA BISNIS - Putra, Kadek Tegar Wiguna; Sugama, I Dewa Gede Dana; Sugama, I Dewa Gede Dana (Kertha Negara : Journal Ilmu Hukum, 2025)
This study aims to describe the mechanism and effectiveness of mediation as an alternative for resolving business disputes. Writing this journal uses the literature study method. Mediation is a dispute resolution method that involves a neutral third party, called a mediator, who does not have the authority to make decisions but helps the disputing parties reach a mutually acceptable agreement. The results of the literature study show that mediation is an effective alternative dispute resolution because the mediation process is carried out behind closed doors, maintaining the privacy and reputation of the disputing parties. Compared to typical court proceedings, mediation tends to be cheaper, less complicated, and more time-saving. In addition, mediation places great emphasis on the future continuity of the relationship between the parties, making it a preferred option for business people to resolve their disputes. Keywords: Alternative Dispute Resolution, Effectiveness of Mediation, Business Disputes